2014
DOI: 10.7747/jfs.2014.30.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Leaching from Leaf Litter of Cropland Agroforest Tree Species of Bangladesh

Abstract: Leaf litter is the main and quick source of organic matter and nutrient to the soil compared to other parts of litter.This study focused on the nutrients (N, P and K) leaching from leaf litter of Melia azadirachta, Azadirachta indica, Eucalyptus camaldulensis, Swietenia macrophylla, Mangifera indica, Zizyphus jujuba, Litchi chinensis, Albizia saman, Artocarpus heterophyllus, Acacia auriculiformis, Dalbergia sissoo and Khaya anthotheca as the common cropland agroforest tree species of Bangladesh. About (9 to 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…5), similar to the findings of Kaba (2017), but contrary to other workers (e.g. Lin et al 2007;Majumder et al 2010;Hossain et al 2011;Hasanuzzaman and Mahmood 2014) who observed an increase and attributed it to microbial or non-microbial immobilisation.…”
Section: Nutrient Release Dynamicssupporting
confidence: 88%
See 1 more Smart Citation
“…5), similar to the findings of Kaba (2017), but contrary to other workers (e.g. Lin et al 2007;Majumder et al 2010;Hossain et al 2011;Hasanuzzaman and Mahmood 2014) who observed an increase and attributed it to microbial or non-microbial immobilisation.…”
Section: Nutrient Release Dynamicssupporting
confidence: 88%
“…The rate of litter decomposition in an ecosystem depends on the interaction of a variety of factors such as litter quantity and quality (e.g. concentration of nitrogen, phosphorus, lignin, polyphenols and their ratios), variety, composition and activities of decomposers, climatic conditions (particularly temperature and humidity), soil nutrient content and availability, age of vegetation or plantation, and vegetation and management types (Dawoe et al 2010;Triadiati et al 2011;Hasanuzzaman and Mahmood 2014;Kaba 2017;Naik et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The annual litterfall results reported in this study for both organic and conventional cocoa systems are higher than the values (3.3 -7.0 Mg ha -1 yr -1 ) reported for most tropical and temperate forests (Zhang et al, 2014), secondary mixed forests (4.2 ± 0.2 Mg ha -1 yr -1 ) in Thailand (Podong et al, 2013), cocoa and kola plantations (4.7 -7.3 Mg ha -1 yr -1 ) in Nigeria (Muoghalu and Odiwe, 2011) and cocoa agroforests (5.0 ± 0.4 -10.4 ± 0.6) in the Ashanti region of Ghana (Dawoe et al, 2010). But similar amounts of annual litterfall similar to our results have also been reported for agroforests and forest ecosystems in Tanzania (Becker et J o u r n a l P r e -p r o o f al., 2015), Indonesia (Triadiati et al, 2011), Central Africa (Averti and Dominique, 2011) and Bangladesh (Hasanuzzaman and Mahmood, 2014). These differences (organic versus conventional cocoa systems) in mean annual litterfall production are possibly due to differences in tree species composition and diversity, plantation age, canopy cover and soil characteristics (Kumar, 2008;Averti and Dominique, 2011;Triadiati et al, 2011).…”
Section: Annual Litterfall and Nutrient Returnmentioning
confidence: 99%
“…Leaf litter is the main and fastest source of organic matter and nutrient to the soil compared to other litter types [6,18,19]. The nutrients in litter were added to the soil through microbial decomposition and physical leaching of soluble components followed by microbial oxidation of refractory components [18,[20][21][22]. However, the amount of nutrient addition through litter decomposition varies from species to species [20,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a considerable amount of nutrients are returned to the soil through litter fall which has an important role in the biogeochemical cycling of nutrients [13,14]. Litter improves soil quality through adding the organic matter and nutrients to the soil [15][16][17].…”
Section: Introductionmentioning
confidence: 99%